Exome sequencing unravels genetic variants associated with chronic kidney disease in Saudi Arabian patients. Issue 12 (8th October 2022) - Al‐Hamed, Mohamed H.; Hussein, Maged H.; Shah, Yaser; Al‐Mojalli, Hamad; Alsabban, Essam; Alshareef, Turki; Altayyar, Ali; Elshouny, Samir; Ali, Wafaa; Abduljabbar, Mai; AlOtaibi, Afaf; AlShammasi, Amal; et al.
Abstract: The use of genetic testing within nephrology is increasing and its diagnostic yield depends on the methods utilized, patient selection criteria, and population characteristics. We performed exome sequencing (ES) analysis on 102 chronic kidney disease (CKD) patients with likely genetic kidney disease. Patients had diverse CKD subtypes with/without consanguinity, positive family history, and possible hereditary renal syndrome with extra‐renal abnormalities or progressive kidney disease of unknown etiology. The identified genetic variants associated with the observed kidney phenotypes were then confirmed and reported. End‐stage kidney disease was reported in 51% of the cohort and a family history of kidney disease in 59%, while known consanguinity was reported in 54%. Pathogenic/likely pathogenic variants were identified in 43 patients with a diagnostic yield of 42%, and clinically associated variants of unknown significance (VUS) were identified in further 21 CKD patients (21%). A total of eight novel predicted pathogenic variants and eight VUS were detected. The clinical utility of ES within the nephrology clinic was demonstrated allowing patient management to be disease‐specific. In this cohort, ES detected a diagnostic molecular abnormality in 42% of patients with CKD phenotypes. Positive family history and high rates of consanguinity likely contributed to this high diagnostic yield.